An Adaptive Modulation in Millimeter-Wave Communication System for Tropical Region - Suwadi Suwadi; Gamantyo Hendrantoro; Wirawan Wirawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
The dominant propagation factor affecting the outage and the spectral efficiency of millimeter-wave communication systems operating at frequencies 30 GHz is rain attenuation. An adaptive modulation is proposed to improve the outage and spectral efficiency performance of the system. This paper presents an analytical procedure for the evaluation of the outage and spectral efficiency of the system in Indonesia with heavy rain rate. By comparing analytic and simulation a validation was conducted. The results show that adaptive modulation can significantly improve the outage and the spectral efficiency performance of the system, for links with long distance.